Spatial Variations of Surface Water Quality in Hau Giang Province, Vietnam Using Multivariate Statistical Techniques: DOI: 10.32526/ennrj.18.4.2020.38 - Thanh Giao, Nguyen (Environment and Natural Resources Journal, 2020)
This study assessed the surface water monitoring system in Hau Giang Province in 2019. The monitoring data for pH, temperature, total suspended solids (TSS), dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammonium (NH4+_N), nitrite (NO2-_N), nitrate (NO3-_N), orthophosphate (PO43-_P), coliforms, and iron (Fe) were collected from the Department of Natural Resources and Environment, Hau Giang Province, Vietnam. The results were compared with the national technical regulation on surface water quality (QCVN 08-MT: 2015/BTNMT). Then, these parameters were used to determine the locations and parameters for water quality monitoring using multivariate analyses including cluster analysis (CA) and principal component analysis (PCA). The results indicated that the main concerns for the quality of water in the canal of Hau Giang Province were organic matter (high BOD and COD), nutrients (NH4+_N, NO2-_N, PO43-_P), coliforms and iron. The CA results showed that 42 monitoring locations could be decreased to 26 locations, reducing monitoring costs by up to 32%. The PCA identified 12 sources of pollution, of which three main sources were PC1, PC2 and PC3 accounting for 75.6% of the variation in water quality. PCA findings showed that all the current water variables in the 2019 monitoring program were significant. The present study could help local environmental managers to reconsider the selected locations and parameters in the environmental monitoring program.